PENGARUH PENGGUNAAN MODEL THINK PAIR AND SHARE TERHADAP HASIL BELAJAR MATEMATIKA BAGI SISWA KELAS V DI SD NEGERI GROJOGAN - Ratih Trias Finiza; A. A. Sujadi (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of descriptive research is to determine the trends in mathematics learning outcomes using Think Pair and Share learning models and Expository learning models. Comparatively to find out the effect of Think Pair and Share learning model and Expository learning model on the mathematics learning outcomes of class V students of SD Negeri Grojogan.Â The hypothesis proposed in this study is that there is a positive influence on the Think Pair and Share learning model on the results of mathematics learning in fifth grade students of SD Negeri Grojogan in the academic year 2017/2018. The type of research used is a quasi experiment. The population of the study was the fifth grade students of Grojogan State Elementary School totaling 45 students, while the sample of this study was students of class V B as the experimental class with the number of students 22 and class V A as the control class with the number of students 23. Data collection techniques used documentation and test techniques. The data analysis technique uses descriptive analysis and hypothesis testing using the t test which is preceded by the analysis prerequisite test, namely the balance test, variant homogeneity test and distribution normality test.Â Descriptive research results show that the tendency of mathematics learning outcomes using Think Pair and Share learning models is high with an average score of 19.73 and the tendency of mathematics learning outcomes using the Expository learning model is classified as moderate with an average score of 15.13. The results of the analysis obtained a value of tcountÂ = 6.074 with a value of p = 0,000 <0.01. Thus, there are very significant differences in mathematics learning outcomes of students who are taught using Think Pair and Share learning models and Expository learning models. By looking at the average learning outcomes using Think Pair and Share learning models 19.73 and those using the Expository learning model 15.13, the Think Pair and Share learning model has a more positive effect on improving mathematics learning outcomes than the Expository learning model. Based on the results of research, schools should add reading references about Think Pair and Share learning models that can be used as a reference in the implementation of learning.